2019
DOI: 10.1111/liv.14299
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir‐containing regimens are safe and effective in the treatment of HCV patients with moderate to severe renal impairment

Abstract: Background and Aims This study aimed to assess the safety and efficacy of sofosbuvir (SOF)‐based regimens in patients with moderate to severe renal impairment; a subject which has been questioned by many investigators with conflicting results. Methods This is a real‐life multicentre retrospective cohort study on 4944 chronic Hepatitis C virus (HCV) patients with chronic kidney disease (CKD) (eGFR <60 mL/min/1.73 m2) who received SOF‐based therapy in specialized treatment centres affiliated to the National Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Sofosbuvircontaining regimens were shown to be safe in patients with moderate to severe renal impairment, including those with estimated glomerular filtration rate (eGFR) <30 ml/min/1.73 m 2 and those with end-stage renal disease requiring haemodialysis, with or without hepatic decompensation. 27 A recent study has confirmed the safety of sofosbuvir in patients with stage 4-5 kidney disease who were not on dialysis. 28 Sofosbuvir exposure is not significantly changed in patients with mild liver impairment (Child-Pugh A cirrhosis), but it is increased 2.3-fold in those with moderate liver impairment (Child-Pugh B cirrhosis).…”
Section: Sofosbuvirmentioning
confidence: 93%
“…Sofosbuvircontaining regimens were shown to be safe in patients with moderate to severe renal impairment, including those with estimated glomerular filtration rate (eGFR) <30 ml/min/1.73 m 2 and those with end-stage renal disease requiring haemodialysis, with or without hepatic decompensation. 27 A recent study has confirmed the safety of sofosbuvir in patients with stage 4-5 kidney disease who were not on dialysis. 28 Sofosbuvir exposure is not significantly changed in patients with mild liver impairment (Child-Pugh A cirrhosis), but it is increased 2.3-fold in those with moderate liver impairment (Child-Pugh B cirrhosis).…”
Section: Sofosbuvirmentioning
confidence: 93%
“…While recent Egyptian study conducted by Eleterby et al had studied the efficacy of sofosbuvir based regimen in chronic HCV patients with CKD with eGFR of less than 60 mL/min/1.73 m2, and they concluded that SVR was achieved in 97.5% of their study population, and that 18 patients of their patients had improved renal function at end of therapy, they also documented that patients group with more severe renal disease and those on dialysis showed lower SVR (80%) and they concluded that these regimens are safe and effective in treating patients suffering from chronic HCV with moderate to severe renal impairment. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…A drop in eGFR from baseline greater than 10 mL/min/1.73m 2 was noted in 16.5% (235/1427) and 15.9% (77/485) among patients with baseline stage 3 CKD who received sofosbuvir/ledipasvir with and without ribavirin, respectively [53]. Further evidence based on real life studies has been recently established [54][55][56][57][58][59]…”
Section: Sof-based Daas (Real World Studies)mentioning
confidence: 97%